Soluble polybenzimidazoles with intrinsic porosity: synthesis, structure, properties and processability - Kumar, Vikas; Chatterjee, Shyambo; Sharma, Pragati; Chakrabarty, Suman; Avadhani, Chilukuri V.; Sivaram, Swaminathan (56Journal of Polymer Science Part A-Polymer Chemistry, 2018)
We have explored two novel comonomers, namely, 4,16-dicarboxyl[2.2]paracyclophane and 5,5,6,6-tetraamino-3,3,3,3-tetramethyl-1,1-spirobi[indane], for the synthesis of co-polybenzimidazoles (co-PBIs) with intrinsic porosity. Both these monomers possess twisted structures that can lead to awkward macromolecular shapes that cannot pack efficiently. The consequences of introducing these two monomers on the structure and properties of PBIs are reported. The random copolymers synthesized are amorphous and possess glass transition temperatures (T(g)s) greater than 400 degrees C. T-g decreases with increasing comonomer content indicating an increase in fractional free volume. The copolymers have low surface area. TEM and BET measurements show evidence of mesopore formation. The copolymers show significant carbon dioxide adsorption. Single chain molecular dynamics simulation of 24-mer repeat units shows intramolecular void spaces arising as a result of distorted polymer chain with reduced conformational mobility. These studies define a new synthetic strategy for bottoms-up synthesis of PBIs with intrinsic porosity. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1046-1057

Lithium speciation in the LiPF6/PC electrolyte studied by two dimensional heteronuclear overhauser enhancement and pulse field gradient diffusometry NMR - Kumar, Vikas; Reddy, R. Ravikanth; Kumar, B. V. N. Phani; Avadhani, Chilukuri V.; Ganapathy, Subramanian; Chandrakumar, Narayanan; Sivaram, Swaminathan (Journal of Physical Chemistry C, 2019)
Electrolytic dissociation of lithium hexafluorophosphate (LiPF6) in the nonaqueous cyclic propylene carbonate (PC) has been investigated in the wide range of concentration (0.05-3.5 M) by Li-7 solution-state nuclear magnetic resonance (NMR) spectroscopy. Two-dimensional heteronuclear Overhauser enhancement spectroscopy NMR experiments have not only enabled the cation solvation and ion-pairing to be directly monitored but additionally evidence anion solvent interaction at higher concentrations (>1.2 M) of the PC electrolyte. Preliminary analysis of kinetic nOe data has been made to determine site-dependent cross-relaxation rates for the spatial interaction of the solvent with the Li+ cation and the PF6- anion. The concentration dependence of the Li-7 NMR self-diffusion coefficient (D-self), determined using very strong pulsed magnetic field gradients (similar to 1700 Gauss/cm), depicts two breaks to mark the solvation and ion-pairing events in a distinct manner. This in turn has aided the determination of solvent coordination number and average sizes of solvated and ion-paired clusters. Our results indicate that in the contact ion pair (CIP)-dominated electrolyte (>2 M), lithium-ion mobility across the solvated and ion-paired environments appears to be inhibited which makes the spectral distinction of solvated and ion-paired environments possible. The concentration dependence of the Li-7 NMR spectral and diffusometry data is in striking correspondence with that of bulk conductivity measurements and point to the detrimental effect of CIP aggregates in impeding the ionic conductivity at high salt concentrations. These results have significance in understanding the structure and dynamics of lithium-ion solvates that are ubiquitous in the working environment of a lithium-ion battery.

Stabilization of bis(chlorogermyliumylidene)s within bifunctional PNNP ligand frameworks and their reactivity studies - Sahoo, Padmini; Raut, Ravindra K.; Maurya, Devesh; Kumar, Vikas; Rani, Pooja; Gonnade, Rajesh G.; Majumdar, Moumita (Dalton Transactions, 2019)
The diiminodiphosphine (L-im) and diaminodiphosphines (l-NH and l-NMe) with a bifunctional PNNP ligand framework have been employed to host two [GeCl](+) units leading to the formation of bis(chlorogermyliumylidene) 1-3, respectively. The synthetic route involves a 1:2 stoichiometric reaction between the PNNP ligand and GeCl(2)dioxane and the subsequent addition of two equivalents of chloride abstracting agent. Compound 1 is unstable towards coordinating solvents and Lewis bases, resulting in the displacement of the GeCl unit and the formation of rearranged products 4 and 5. However, the diaminodiphosphine coordinated Ge(ii) bis(monocation)s 2 and 3 proved to be stable and revealed their electrophilic behaviour towards the Lewis bases studied.

Untargeted metabolomics reveals alterations in metabolites of lipid metabolism and immune pathways in the serum of rats after long-term oral administration of Amalaki rasayana - Kumar, Vikas; Kumar, A. Aneesh; Joseph, Vinod; Dan, Vipin Mohan; Jaleel, Abdul; Kumar, T. R. Santhosh; Kartha, Chandrasekharan C. (Molecular and Cellular Biochemistry, 2020)
Amalaki rasayana, a traditional preparation, is widely used by Ayurvedic physicians for the treatment of inflammatory conditions, cardiovascular diseases, and cancer. Metabolic alterations induced by Amalaki rasayana intervention are unknown. We investigated the modulations in serum metabolomic profiles in Wistar rats following long-term oral administration of Amalaki rasayana. Global metabolic profiling was performed of the serum of rats administered with either Amalaki rasayana (AR) or ghee + honey (GH) for 18 months and control animals which were left untreated. Amalaki rasayana components were confirmed from AR extract using HR-LCMS analysis. Significant reductions in prostaglandin J2, 11-dehydrothromboxane B2, and higher levels of reduced glutathione and glycitein metabolites were observed in the serum of AR administered rats compared to the control groups. Eleven different metabolites classified as phospholipids, glycerophospholipids, glucoside derivatives, organic acids, and glycosphingolipid were exclusively observed in the AR administered rats. Pathway analysis suggests that altered metabolites in AR administered rats are those associated with different biochemical pathways of arachidonic acid metabolism, fatty acid metabolism, leukotriene metabolism, G-protein mediated events, phospholipid metabolism, and the immune system. Targeted metabolomics confirmed the presence of gallic acid, ellagic acid, and arachidonic acid components in the AR extract. The known activities of these components can be correlated with the altered metabolic profile following long-term AR administration. AR also activates IGF1R-Akt-Foxo3 signaling axis in heart tissues of rats administered with AR. Our study identifies AR components that induce alterations in lipid metabolism and immune pathways in animals which consume AR for an extended period.
Keywords: Amalaki rasayana; Ayurvedic medicines; Leukotriene metabolism; Lipid metabolism; Metabolic profiling

Intramolecularly double-donor-stabilized stannylene and its coordination towards Ag(I) and Au(I) centers - Chibde, Purva; Raut, Ravindra K.; Kumar, Vikas; Deb, Rahul; Gonnade, Rajesh; Majumdar, Moumita (Chemistry-An Asian Journal, 2021)
The intramolecularly double-donor-stabilized stannylene 1 has been synthesized from the salt-metathesis reaction between two equivalents of lithium pyridine ene-amide L1 and SnCl2. Compound 1 exhibits dipolar behavior when reacted with B(C6F5)(3) leading to the zwitterionic compound 2. The reaction of 1 with one equivalent and 0.5 equivalent of AgOTf (OTf=trifluoromethane sulfonate) result in the formation of a stannylene-AgOTf complex 3 and a homoleptic distannylene-silver ionic complex 4, respectively. Analogous to complex 4, the gold(I) complex 5 has been synthesized from the reaction between two equivalents of 1 and 0.5 equivalent of AuCl.SMe2/Me3SiOTf. Complex 5 is the first example of homoleptic stannylene-Au(I) ionic complex among the very scarce reports on stannylene-gold(I) coordination complexes. All compounds have been structurally characterized using single crystal X-ray crystallography. Solution-state characterization have been performed using multinuclear NMR techniques. Detailed DFT calculations on the optimized geometries 1 o, 3 o-5 o reveal the change in sp- hybridization on the pyramidal Sn(II) center upon metal coordination and their bonding overlaps.
Keywords: coordination; gold cation; hybridization; intramolecular donor; stannylene

Stabilization of the elusive antimony(I) cation and its coordination complexes with transition metals - Kumar, Vikas; Gonnade, Rajesh G.; Yildiz, Cem B.; Majumdar, Moumita (Angewandte Chemie-International Edition, 2021)
Upon stabilization by 5,6-bis(diisopropylphosphino)acenaphthene to form compound 1, the fugitive antimony (I) cation exhibited nucleophilic behavior towards coinage metals. Compound 1 was strategically synthesized at room temperature from SbCl3, the bis(phosphine), and trimethylsilyl trifluoromethanesulfonate taken in a 1:2:3 ratio, whereby the bis(phosphine) plays the dual role of a reductant and a supporting ligand. The generation of 1 involves two-electron oxidation of the ligand to form a P-P bonded diphosphonium dication. Compound 1 was separated from this dication to give both products in pure form in moderate yields. Despite the overall positive charge, the Sb-I site in 1 was found to bind to metal centers, forming complexes with Au-I, Ag-I and Cu-I. Compound 1 reduced Cu-II to Cu-I and formed a coordination complex with the resulting Cu-I species. The effects of the electron-rich bis(phosphine) and the constrained peri geometry in stabilizing and enhancing the nucleophilicity of 1 have been rationalized through computational studies.
Keywords: antimony(I) cation; coordination modes; nucleophilicity; phosphine ligands; reduction

Smallest acyclic tricationic molecule containing a Bis(phosphine)-stabilized low-valent triantimony-based Unit - Mukherjee, Nilanjana; Peerless, Benjamin; Nadurata, Vincent L.; Kumar, Vikas; Sangole, Mayur P.; Singh, Kirandeep; Wiedemann, Haakon T. A.; Kay, Christopher W. M.; Kruk, Robert; Weigend, Florian; Dehnen, Stefanie; Gonnade, Rajesh G.; et al. (Nature Communications, 2026)
Element-element bonded multiply charged cationic species are well known as dimers or small cyclic oligomers in the condensed phase. However, the smallest acyclic version, a trinuclear unit possessing greater than a monocationic charge, has remained elusive. Here we introduce a bis(phosphine) supported low valent triantimony-based tricationic compound as a new entrant in this field. Structural elucidation and electronic understanding reveal a W-shaped tricationic unit comprising of a three-center four-electron sigma-bonded triantimony moiety that is terminally capped by bis(phosphine) ligands, with the central antimony atom having two lone pairs of electrons. The unique counter trianion [Sb(O)2(OTf)4]3- (OTf = CF3SO3) possesses reactive polar Sb delta+-O delta- bonds, the structure of which is determined from single crystal X-ray diffraction analysis. The ensemble of reactive molecular fragments found in this highly charged antimony-based compound makes it thermally unstable. Nonetheless, this fully characterized fleeting species shows a diverse reactivity profile, advancing the isolation of various novel antimony compounds, including the formation of a distinct low-valent antimony-cobalt carbonyl cluster.